Gene Regulation and Metabolism Postgenomic computational approaches - Collado-Vides, Julio; Ed (Ane Books, 2004)
"This book focuses on current computational approaches to understanding the complex networks of metabolic and gene regulatory capabilities of the cell. The contributors look well beyond the state of the art in computational biology to anticipate what biological research will be like in a postgenomic world."--Jacket.